Conflict of Jurisdiction between the Federal Supreme Court and the Administrative Judiciary in Iraq : Analytical Study - Hamzah, Mohammed (Journal of Legal Sciences, 2022)
It is recognized, that the constitutional text is the binding rule for all persons of the state, whether rulers or ruled, with all the contents of the constitutional texts, and thus the three authorities; Legislative, judicial, and executive are bound by the content of these texts, as it is not possible for any of these authorities to confer their own visions and perceptions on the constitutional text, so it is necessary to return to the will of the constitutional founder, in order to clarify the meaning that he seeks by placing that text. This includes the content of Article (93/Third) of the Constitution of Iraq for the year 2005, which referred to the disputes that the Federal Supreme Court is competent to consider. 83) of the amended 1969, one of the issues that arise before the courts, as a result of the interactions that can occur when adapting the legal relationship, and assigning it to one court rather than another, and to the developments witnessed by the Iraqi judicial system after its transition from the unified judicial system to the dual judiciary, Which is a qualitative leap in devoting the functional jurisdiction of the judiciary, as the competencies and their diversity are evidence of the sophistication and diversity of society, but in a case that can be described as rare, we find that there is a conflict of jurisdiction that arose between the Federal Supreme Court and the courts of first instance. The Employees Judiciary Court) in the administrative courts, and this rarely happens in international legal systems, as disputes that occur between courts are often between the courts of the judicial authority or the same degree. In the event of a conflict in jurisdiction between the courts of the ordinary judiciary and the courts of the administrative judiciary, here the authority for appointing the reference can address according to the provisions of the State Council Law of 1979. Or it may occur between the courts of the same judiciary, so the Supreme Court has the final word in this judiciary.